Associations of prenatal metal exposure with child neurodevelopment and mediation by perturbation of metabolic pathways - Ya Xie; Han Xiao; Dejuan Zheng; Gaga Mahai; Yuanyuan Li; Wei Xia; Shunqing Xu; Aifen Zhou (Nature Communications)
Abstract Prenatal exposure to metals has been associated with impaired neurodevelopment in children, but the detailed molecular mechanisms remain largely unknown. Based on the Wuhan Healthy Baby Cohort, China (N = 1088), eleven metals were measured in maternal urine during early pregnancy (13.1 ± 1.1 weeks) and metabolomics profiling was conducted in cord blood. Neurodevelopment was evaluated using the Bayley Scales of Infant Development in 2-year-old children to obtain the mental development index (MDI) and psychomotor development index (PDI). After false discovery rate correction, higher maternal urinary levels of manganese, nickel, aluminum, rubidium, gallium, and the summary score of metals were only significantly associated with lower MDI scores. The weighted quantile sum index of the metal mixture showed a significant inverse association with MDI and PDI scores, with aluminum contributing the most to the associations. Histidine, beta-alanine, purine, and pyrimidine metabolism significantly mediated the above associations, suggesting that disturbances in amino acids, neurotransmitter and neuroendocrine metabolism may be important mediators in contributing to impaired neurodevelopment of children.